To shake the sleeping self : a journey from Oregon to Patagonia, and a quest for a life with no regret - Jenkins, Jedidiah (Convergent Books, 2018)
"From travel writer Jedidiah Jenkins comes a long-awaited memoir of adventure, wonder, and lessons learned while bicycling from Oregon to Patagonia. On the edge of turning thirty, terrified of being funneled into a life he didn't choose, Jedidiah Jenkins quit his dream job and spent the next sixteen months cycling from Oregon to Patagonia. He chronicled the trip on Instagram, where his photos and profound reflections on life soon attracted hundreds of thousands of followers and got him featured by National Geographic and The Paris Review. In this unflinchingly honest memoir, Jenkins narrates his adventure--the people and places he encountered on his way to the bottom of the world--as well as the internal journey that started it all. As he traverses cities, mountains, and exotic locales, Jenkins grapples with the question of what it means to be an adult and with his struggle to reconcile his sexual identity with his conservative Christian upbringing. As he writes in his inspiring search for wonder and a life he could believe in, 'It's not about the bike. It's about getting out of your routine--and that could look like anything'"--